ANALISIS YURIDIS PENETAPAN STATUS ANAK ANGKAT YANG TELAH BERUSIA DEWASA (STUDI PENETAPAN PENGADILAN NOMOR PERKARA: 0486/Pdt.P/2020/PA.Bwi) - Nurillah Harry Putri; Sulistiyantoro, Hariyo (Lex Journal: Kajian Hukum & Keadilan, 2022)
This normative legal research examines the Determination of the Banyuwangi Religious Court Number: 0486/Pdt.P/2020/Pa.Bwi granted the request for the determination of the status of an adopted child submitted by an adopted child who was 41 years old after both his adoptive parents died. The purpose of this study is to determine the basis of the judge's considerations and the legal consequences. The data sources were obtained from literature studies and interviews. This research uses a descriptive qualitative data analysis method. From the results of the study, it was concluded that Determination Number: 0486/Pdt.P/2020/Pa.Bwi is not in accordance with Article 12 Paragraph (1) letter (a) PP Number 54 of 2007 concerning the Implementation of Child Adoption and Article 4 letter (a) and Minister of Social Affairs of the Republic of Indonesia Number: 110/HUK/2009 concerning Requirements for Adoption of Children. Considering that the judge in giving a decision cannot prioritize the legal certainty of regulation, but also considers justice and benefits for the parties concerned. The legal consequences of the stipulation are limited to civil relations in the case of mandatory wills.